2015
DOI: 10.1186/s12936-015-0933-7
|View full text |Cite
|
Sign up to set email alerts
|

High adherence to malaria treatment: promising results of an adherence study in South Kivu, Democratic Republic of the Congo

Abstract: BackgroundIn resource-poor settings, treatment adherence is a major determinant of response to anti-malarial drugs as most are taken at home without medical supervision. Evidence on adherence to artemisinin-based combination therapy (ACT) is limited. The study aimed to measure adherence and identify reasons for non-adherence to a 3-day, fixed-dose combination (FDC) of artesunate–amodiaquine (ASAQ), the first-line treatment for uncomplicated malaria in the Médecins Sans Frontières project in the Shabunda Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Weaknesses in the collection, validation, and reporting of malaria data from ASHAs hampered surveillance efforts [8]. There was no system to verify treatment compliance and parasite clearance from the patients’ blood [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Weaknesses in the collection, validation, and reporting of malaria data from ASHAs hampered surveillance efforts [8]. There was no system to verify treatment compliance and parasite clearance from the patients’ blood [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have evaluated patient adherence to anti-malarial drugs and associated factors. The documented level of patient adherence to ASAQ varies from 48% in Sierra Leone [9] to 75% in the Democratic Republic of Congo [10], to 93% in Ghana [11]. One qualitative study comparing ACT adherence in northern Ghana found that patients preferred AL over ASAQ due to adverse events experienced with ASAQ [12].…”
Section: Introductionmentioning
confidence: 99%
“…1 ): efficacy, access, diagnosis, health service provider practice, and patient adherence [ 1 , 13 ]. Several factors affect implementation at each step, falling into one of the following broader categories: health system, health service provider, and patient [ 14 , 15 ]. Low indicators at any step present a bottleneck to the overall performance of the system.…”
Section: Introductionmentioning
confidence: 99%